Flood hazard assessment in Pemaluan Village due to land use change in IKN (Ibu Kota Nusantara) as the New Capital City of Indonesia - B. Handyastono; M.A. Alghoul; A. Rizki; N.P. Djambek; M.S.B. Kusuma; A.A. Kuntoro; D. Harlan; E.O. Nugroho; H.M. Munthe; M. Hazmi; D.H. Wisanggeni; M.A. Rizqy (Case Studies in Chemical and Environmental Engineering)
Flood is annual disaster in Pemaluan Village however there is no previous flood hazard study in this area. The development of IKN as the New Capital City of Indonesia since 2022 has significant changed the land cover of Pemaluan River catchment area. Meanwhile, flood hazard in Pemaluan Village has been significantly increased in the last two years. This study discuss regarding the influence of the land cover changes due to the IKN development to the flood hazard in Pemaluan River. This study is done based on hydraulic model HEC-RAS 6.5 to assess the flood hazard due to Q50. The model has been calibrated based on March 17, 2023, to fit in the curve number use for the model.Based on the model result in 2019, flood hazard in Pemaluan Village is categorized as follow: 100.17 ha as “very low,” 399.46 ha as “low,” 710.71 ha as “medium,” 287.57 ha as “high,” and 0 ha as “very high,” with a total area of 1497.91 ha. However, this flood hazard has been increased in 2023 as follow: 105.97 ha categorized as “very low,” 396.48 ha as “low,” 721.32 ha as “medium,” 321.39 ha as “high,” and 0 ha as “very high,” resulting in a total inundation area of 1545.16 ha. It is also identified that the main hazard parameter is velocity depth. The model assessment is done for the scenario 20 % IKN development achievement. The next research should be done appropriate to IKN development achievement that not yet avaliable in the present.